Sistem Keamanan Boarding Gate Menggunakan Face Recognition, Fingerprint Dan E-Ktp Berbasis Iot - Nurul Afifah; Retno Devita; Mardiah Masril (Journal of Computer Scine and Information Technology, 2024)
The development of technology using biometrics has become a trend that is currently widely used in the modern era. This involves an identification process using biological information such as fingerprints, retinas, and other body parts. The problem that occurs is the identity check before entering the departure gate which is done manually, such as looking at the E-KTP officer, the passenger's face according to the KTP, and the ticket. Airport officials will ensure that the passenger has the correct ticket, check identity and then compare the similarities between the personal data stated therein, before confirming that the data is the same and meets security requirements before allowing entry onto the plane. The departure gate security system utilizes Esp32-Cam input, Rfid Reader, Fingerprint Sensor and Esp8266 output, Google Sheet, Servo, LED, LCD and Buzzer. Esp32-Cam can verify faces, then the LCD will display information that the face verification was successful, the fingerprint sensor detects fingerprints and the RFID Reader detects E-KTP. This tool is processed with an Arduino Mega 2560 microcontroller as a connection.